Immunological properties of hepatitis B core antigen fusion proteins. - Francis, M J (1990)
The immunogenicity of a 19 amino acid peptide from foot-and-mouth disease virus has previously been shown to approach that of the inactivated virus from which it was derived after multimeric particulate presentation as an N-terminal fusion with hepatitis B core antigen. In this report we demonstrate that rhinovirus peptide-hepatitis B core antigen fusion proteins are 10-fold more immunogenic than peptide coupled to keyhole limpet hemocyanin and 100-fold more immunogenic than uncoupled peptide with an added helper T-cell epitope. The fusion proteins can be readily administered without adjuvant or with adjuvants acceptable for human and veterinary application and can elicit a response after nasal or oral dosing. The fusion proteins can also act as T-cell-independent antigens. These properties provide further support for their suitability as presentation systems for "foreign" epitopes in the development of vaccines.